Ultrasonographic examination of the radial and ulnar nerves after percutaneous cross-wiring of supracondylar humerus fractures in children: a prospective, randomized controlled study - Altay, Mehmet Akif; Erturk, Cemil; Altay, Mehmet; Belhan, Oktay; Isikan, Ugur Erdem (Lippincott Williams & Wilkins, 2011)
In this prospective study, we aimed to find out whether there is a change in the ultrasonographic features of the radial and ulnar nerves as well as clinical outcomes after traditional and lateral percutaneous cross-wiring of the supracondylar humerus fractures in children. Twenty-nine consecutive children with completely displaced Gartland type III supracondylar humerus fractures were treated with the traditional (group T) or lateral (group L) cross-wiring technique. Our findings showed that ultrasonographic features of the radial nerve were not changed in both groups but the ulnar nerve movement was reduced, and the diameter of major axis of the ulnar nerve during elbow flexion was larger (P = 0.040) than in elbow extension in the traditional cross-wiring technique but not in the lateral cross-wiring technique. Lateral cross-wiring technique does not change the ultrasonographic features of the radial and ulnar nerves, and provides satisfactory results. J Pediatr Orthop B 20:334340 (C) 2011 Wolters Kluwer Health vertical bar Lippincott Williams & Wilkins.
Keywords: children; lateral cross-wiring; supracondylar humerus fractures; traditional cross-wiring